Genetic analysis of a morphologically heterogeneous ovarian endometrioid carcinoma. Issue 3 (16th June 2017) - Geyer, Felipe C; Pareja, Fresia; Burke, Kathleen A; Schultheis, Anne M; Hussein, Yaser R; Ye, Jiqing; De Filippo, Maria R; Marchio, Caterina; Macedo, Gabriel S; Piscuoglio, Salvatore; Lim, Raymond S; Toy, Eugene; et al.
Abstract : Aims: Low‐grade ovarian endometrioid carcinomas may be associated with high‐grade components. Whether the latter are clonally related to and originate from the low‐grade endometrioid carcinoma remains unclear. The aim of this study was to use massively parallel sequencing to characterize the genomic landscape and clonal relatedness of an ovarian endometrioid carcinoma containing low‐grade and high‐grade components. Methods and results: DNA samples extracted from each tumour component (low‐grade endometrioid, high‐grade anaplastic and high‐grade squamous) and matched normal tissue were subjected to targeted massively parallel sequencing with the 410‐gene Memorial Sloan Kettering‐Integrated Mutation Profiling of Actionable Cancer Targets (MSK‐IMPACT) sequencing assay. Somatic single nucleotide variants, small insertions and deletions, and copy number alterations were detected with state‐of‐the‐art bioinformatics algorithms, and validated with orthogonal methods. The endometrioid carcinoma and the associated high‐grade components shared copy number alterations and four clonal mutations, including SMARCA4 mutations, which resulted in loss of BRG1 protein expression. Subclonal mutations and mutations restricted to single components were also identified, such as distinct TP53 mutations restricted to each histological component. Conclusions: Histologically distinct components of ovarian endometrioid carcinomas may show intratumour genetic heterogeneity but be clonally related, harbouring a complex clonal composition. In the present case, SMARCA4 mutations were probably early events, whereas TP53 somatic mutations were acquired later in evolution.